Making Direct Air Capture Affordable; Technology, Market and Regulatory Approaches - Beaumont, Maximus L. L. (Frontiers in Climate, 2022)
Direct Air Capture (DAC) is an important solution to curb global warming and enable a circular economy. As fossil fuels dwindle, carbon for commodities such as plastic, cement, steel and liquid fuel, will need to come from somewhere. With the low cost of industrial CO2 (roughly $80 a ton) as well as the low value of most carbon credits, making DAC-produced CO2 competitive at scale is almost impossible. But what if we could scale DAC processes in markets that make sense now, building on learnings as we go while making industries less carbon intensive? The first such application is air quality and energy efficiency in indoor spaces. DAC technology can stabilise CO2 and water levels inside indoor environments to enhance the recirculation rate of internal air, thereby saving significant energy for the HVAC. Another application is the use of small-scale DAC units – providing CO2 at the scale of kilos a day rather than tons, taking advantage of the high CO2 price at that scale as well as B2C markets that otherwise rely on bottled CO2. The approach is called Distributed-DAC or DDAC (analogous to distributed solar). DAC processes need to be developed but to scale our learnings and drive down costs, we must fund R&D and introduce a significant carbon tax. Finally, interesting new developments such as electro-swing and humidity-swing carbon capture, have the potential to drastically decrease the energy footprint of DAC (its main cost driver), paving the way to make DAC affordable.